Qualidade na prestação de serviços: uma análise da satisfação do cliente com o sistema Gamerhouse em Parintins/AM - Eleutério Júnior, Alfredo Silveira (Brasil, 2023)
Service quality is one of the crucial aspects for the success of any business. Companies committed to service quality are able to build a positive opinion and build long-term customer loyalty. This monograph discusses: Quality in the provision of services: an analysis of customer satisfaction with the Gamerhouse system in Parintins/AM, permeated by the general objective: to analyze the quality of services provided by Epicentro Informática within the scope of its sub-operation GamerHouse. As for the specific objectives, they aim to characterize the profile of the operation and the market niche in which it operates, mentioning customer satisfaction with the services provided and, finally, to evaluate the constraints observed by customers for the perception of quality in the services provided. It is a qualitative and quantitative study, bibliographically based on researchers and authors such as: Oliveira (2007), Souza (2021), Moura (1997), Chiavenato (1994), among others. As a data collection instrument, a closed questionnaire was applied. Customers who attend GamerHouse highly value comfort and other aspects related to quality, so being in agreement with what the customer expects can be a way to stand out in the market and gain competitive advantage. In addition, the quality of customer service is essential to stay ahead in the follow-up, building customer loyalty and making them return to the establishment on other occasions, is one of the greatest objectives in the service sector. Companies that invest in quality are able to attract more customers and stand out in the market, thus ensuring a prominent position in the GamerHouses sector.